Biomasselectrochemical integrated system for distillery wastewater treatment with electricity generation using anaerobic mixed consortium in microbial fuel cells. (2015) - Geetha, K.; Raj, S. Amal
The electricity generation and industrial wastewater treatment using microbial fuel cells (MFCs) with primary treated distillery wastewater as substrate and permanganate as cathodic electron acceptor was studied. Initially, low voltage (0.625 V) and current (2.9 mA) were obtained at a substrate loading of 2, 680 mg COD l −1 and further increased (1.165 V and 5.40 mA) at 4, 360 mg COD l −1 with the provided larger anode surface area and the cathode electron acceptor. As a wastewater treatment, 85% COD was removed at a 2, 680 mg COD l −1, whereas at 4, 360 mg COD l −1 57% of COD removal was observed. During electrochemical oxidation, 24.3% and 36% of melanoidins decolourisation with 41.8% and 31% of coulombic efficiency were also achieved at 2, 680 mg COD l −1 and 4360 mg COD l −1 due to the biocatalytic activity of mixed bacterial consortium. This study shows the capability of MFC system to treat the highorganic load as well as generation of energy using biocatalytic oxidation.